A powerhouse of a man : Tom Farrell : a biography of Rolf Everist Farrell - Mooney, Christopher, 1959-; University of Newcastle (N.S.W.). Tom Farrell Institute for the Environment (Melbourne, Victoria : Brolga Publishing, 2015)
"Tom Farrell, champion for Newcastle and champion for the Hunter, was a man ahead of his times. As an effective team player, he worked tirelessly for his community over five decades. The result: the establishment and protection of significant green areas in and around Newcastle (Including Blackbutt, Green Point, Mount Sugarloaf), the foundation of the Newcastle University and the success of key institutions lkie the Newcastle District Abattoir and the Greater Building Society). In meeting the various challenges, Tom showed himself as a powerhouse of a man."--Back cover.
"Tom Farrell Institute for the Environment University of Newcastle"--Title page.
Includes bibliographical references and index.
Keywords: Farrell, Tom, -- 1904-1996.; University of Newcastle (N.S.W.) -- History; Entrepreneurship -- New South Wales -- Newcastle; Environmentalists -- Australia -- Biography; Journalists -- Australia -- Biography; War correspondents -- Australia -- Biography; Newcastle (N.S.W.) -- Social conditions -- History; Newcastle (N.S.W.) -- Social conditions; Hunter Valley (N.S.W.) -- Social conditions -- History; Hunter Valley (N.S.W.) -- Social conditions; Hunter River Valley (N.S.W.) -- Social conditions -- History; Hunter River Valley (N.S.W.) -- Social conditions; Australian